Membincang Gerakan Ilmu Agama dan Filsafat Pada Masa Abbasiyah - Nanang Tantowi; Azhar Fakhru Rijal; Khaerul Wahidin (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2021)
This article analyzes the traces of the movement of religious science and philosophy in the golden period in Islamic history, namely during the Abbasid Dynasty. During that period, Islam experienced its heyday and contributed to the scientific aspect; not only for the Muslim community but also for the non-Muslim community in the world. The research method in this paper uses a descriptive-analytic method by first tracing the religious literature related to the research subject, and then analyzing it critically. Several research findings from this research include the revealing of supporting factors that influenced the achievement of Islamic civilization in the Abbasid Dynasty era through scientific movements, such as government support for Islamic scholarship (manuscript translation projects). Meanwhile, when viewed at the time of Caliph al-Mamun, the role of the Muktazilah school, which at that time became the official school of government, seemed very influential for religious and scientific movements. This is because the Muktazilah school emphasizes many aspects of rationality in religion.